Gastrointestinal Disease in Patients with Common Variable Immunodeficiency: A Retrospective Observational Study. Issue 4 (25th February 2019) - Khan, Rishad; Habbal, Mohamad; Scaffidi, Michael A; Bukhari, Abbas A; Rumman, Amir; Al Ghamdi, Sarah; Betschel, Stephen D; Grover, Samir C
Abstract: Background: Gastrointestinal (GI) symptoms are common among patients with common variable immunodeficiency disorder (CVID) yet remain poorly understood. Aims: The aim of this study was to characterize the demographic, clinical, endoscopic and histologic features of patients with CVID and GI symptoms. Methods: We conducted a retrospective observational study of all patients with CVID at a large Canadian tertiary care centre between January 2000 and May 2018. Results: We included 95 patients with CVID. The mean age of patients at the time of CVID diagnosis was 38.2(±16.0). Fifty-three (56%) patients were female. Sixty-four (67%) patients had GI symptoms, with a mean age of onset for GI symptoms of 43.4(±15.1) years. The most common symptoms were bowel movement changes ( n = 55 [58%]) and abdominal pain ( n = 44 [46%]). Patients with GI symptoms were more likely to have anemia ( n = 23 [36%] versus n = 3 [10%], P = 0.0129), iron deficiency ( n = 16 [25%] versus n = 2 [7%], P = 0.0481), and have received GI antibiotics ( n = 37 [58%] versus n = 0, P < 0.0001) and proton pump inhibitors for reflux ( n = 24 [38%] versus n = 3 [10%], P = 0.0067). The most common GI infections were Giardia lamblia ( n = 14 [15%]) and Clostridium difficile ( n = 4 [4%]). Forty-three (45%) patients with GI symptoms underwent colonoscopy, esophagogastroduodenoscopy or both. The most common findings were inflammation, nodular lymphoid hyperplasia, reduced plasma cells and increased intraepithelial lymphocytes. Conclusions: This is the largest study on CVID patients in a North American setting. The majority of patients experienced GI symptoms. Future studies should study response to treatment for GI disease among patients with CVID.